Metacognition and Critical Thinking Among Indonesian College Students: Examining the Role of Cognitive Load as a Moderating Factor - Nur Amin Barokah Asfari; Anjarie Dharmastuti; Rizka Fibria Nugrahani; Laila Indra Lestari; Callista Justine Margandhi; Clay Alcander Marchelius Teguh (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study examined whether cognitive load moderates the relationship between metacognition and critical thinking among students in Indonesia. A total of 201 undergraduate and diploma students participated by completing an online questionnaire using the Indonesian version of the Metacognitive Awareness Inventory (MAI), the Leppink et al. adaptation of the Cognitive Load Scale, and the Sosu adaptation of the Critical Thinking Disposition Scale. Results showed that metacognition had a significant positive effect on critical thinking (p<.001), explaining approximately 47-50% of the variance across models. However, intrinsic, extraneous, and germane cognitive load did not significantly moderate this relationship. The interaction between metacognitive awareness and critical thinking disposition remains stable across varying levels of perceived cognitive load. These findings highlight metacognition as a robust predictor of critical thinking disposition and suggest that perceived cognitive load may not substantially alter this relationship at the dispositional level. Rather than contradicting Cognitive Load Theory, the results refine its applicability by indicating that cognitive load effects may be more observable in performance-based contexts. Future research may explore whether cognitive load exerts stronger moderating effects on performance-based critical thinking tasks under experimentally manipulated conditions.